A >1300 km late Pan-African metamorphic belt in NE China: New evidence from the Xing'an block and its tectonic implications - Zhou, Jian-bo; Wilde, Simon; Zhang, X.; Zhao, G.; Liu, F.; Qiao, D.; Ren, S.; Liu, J. (Elsevier Science BV, 2011)
The Xing'an Block is one of several fault-bounded crustal units in northern China located along the southeastern margin of the Central Asian Orogenic Belt (CAOB) and includes the Great Xing'an Range. The basement rocks constitute a khondalitic sequence of sillimanite- and garnet-bearing gneisses, hornblende–plagioclase gneiss and felsic paragneiss named the Xinghuadukou Complex. LA-ICP-MS zircon U–Pb dating of a sillimanite gneiss from Hanjiayuan indicates high-grademetamorphismoccurred at 496±3 Ma,with several older detrital zircon grains with ages extending from678±8 to 1373±17Ma.Asample of hornblende–plagioclase gneiss fromthe northern part of the Xinghuadukou Complex yields a metamorphic age of 496±7 Ma, whereas igneous zircon core ages range from601±15 to 1637±23Ma.Another sample of hornblende–plagioclase gneiss fromfarther south in the Xinghuadukou Complex yields a metamorphic age of 495±5 Ma, and magmatic core ages of 546±4 Ma. These data indicate that high-grade metamorphism occurred at ~500 Ma and that several earlier magmatic events are recorded in the area, including some in the Neoproterozoic. These new age data, togetherwith other recent data obtained fromthe Erguna, Songliao, Jiamusi and Khanka blocks, establish a N1300 kmPan-African khondalite belt along the southern margin of the CAOB.